2018
DOI: 10.1097/brs.0000000000002482
|View full text |Cite
|
Sign up to set email alerts
|

Thoracolumbar Intervertebral Disc Area Morphometry in Elderly Chinese Men and Women

Abstract: 3.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…On the other hand, for the vertebral bodies, lower BMD was associated with a decrease of vertebral anterior/middle/ posterior height, but not vertebral anterior-posterior diameter; lower BMD was associated with a decrease in vertebral volume, and an increased biconcavity index (15). Our 4-year longitudinal follow-up study with radiographs shows osteopenia and osteoporosis are associated with faster disc area decrease in both thoracic spine and lumbar spine, and both for both males and females (24). We can naturally assume that a decreased disc volume (as measured with MRI) and decreased disc lateral area (as measured with radiograph) are biomarkers of disc degeneration.…”
mentioning
confidence: 87%
“…On the other hand, for the vertebral bodies, lower BMD was associated with a decrease of vertebral anterior/middle/ posterior height, but not vertebral anterior-posterior diameter; lower BMD was associated with a decrease in vertebral volume, and an increased biconcavity index (15). Our 4-year longitudinal follow-up study with radiographs shows osteopenia and osteoporosis are associated with faster disc area decrease in both thoracic spine and lumbar spine, and both for both males and females (24). We can naturally assume that a decreased disc volume (as measured with MRI) and decreased disc lateral area (as measured with radiograph) are biomarkers of disc degeneration.…”
mentioning
confidence: 87%
“…However, such grading is subjective and difficult to use for epidemiological studies. We developed a Disc Area Index for Lumbar spine (DAIL) index, which quantitatively classifies lumbar disc space into normal disc height or DSN (3). DAIL for each intervertebral level is calculated using Eq.…”
Section: Osteoporosis Is Positively Associated With Intervertebral Disc Degenerationmentioning
confidence: 99%
“…The relationship between LBP and woman gender has been shown in various studies (Troussier et al, 1999[ 36 ]; Schneider et al, 2006[ 34 ]; Bejia et al, 2005[ 6 ]; Wáng et al, 2016[ 38 ]; Yang et al, 2016[ 40 ]). Wáng et al (2018[ 37 ]) indicated that among all age groups, the prevalence of LBP is higher in women compared with men (Wáng et al, 2018[ 37 ]). Similarly, this developed scale is able to differentiate these two groups by giving higher scores of women.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, this developed scale is able to differentiate these two groups by giving higher scores of women. Wáng et al also identified the psychological factors as one of the possible causes for the higher prevalence of LBP in women compared with men (Wáng et al, 2018[ 37 ]). In this study, it was the psychosocial sub-scale that revealed the difference in prevalence of LBP between women and men.…”
Section: Discussionmentioning
confidence: 99%